The Character of the Muscarinic Receptors in Different Regions of the Rat Brain - Birdsall, N J; Hulme, E C; Burgen, A (Proceedings of the Royal Society of London. Series B, Containing papers of a biological character, 1980)
The binding characteristics of muscarinic receptors have been critically examined in six regions of the rat brain. The binding curves of antagonists are similar for all six areas but the binding curves of agonists show large differences. It is shown that in all regions there are three classes of receptors with similar binding characteristics but that these are present in different proportions. The binding constants to the three receptor types of a range of agonists were examined and evidence was produced in support of the theory that the subclasses of brain receptors are due to a single receptor subunit subject to different conformational constraints.